2006
DOI: 10.1136/hrt.2005.085431
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of emergent transcatheter transplantation of stem cells for treatment of acute myocardial infarction (TCT-STAMI)

Abstract: Emergent intracoronary transplantation of bone marrow mononuclear cells after AMI is practicable, and it improved cardiac function, prevented myocardial remodelling and increased myocardial perfusion at six months' follow up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 152 publications
(70 citation statements)
references
References 12 publications
2
68
0
Order By: Relevance
“…Subgroup analysis suggested that the benefit was greatest in patients with the worst LVEF at baseline. In the study conducted by Ge et al, 7 the mean LVEF increased by about 5% in the BMC group (from 53.8%±9.2% at baseline to 58.6%±9.9% at follow-up, P<.05), while LVEF decreased in the control group (from 58.2%±7.5% at baseline to 56.3%±3.5% at follow-up). In the study conducted by Suárez de Lezo et al, 4 the average increase in the ejection fraction exceeded 20% following intracoronary BMC treatment, the largest improvement reported to date (baseline: 37%±5%, followup: 58%±920%), while a significantly smaller increase (6%, P = .003) was observed in the control group (baseline: 39%±6%, follow-up: 45%±8%).…”
Section: Lvef Change Noted In Individual Studiesmentioning
confidence: 86%
See 4 more Smart Citations
“…Subgroup analysis suggested that the benefit was greatest in patients with the worst LVEF at baseline. In the study conducted by Ge et al, 7 the mean LVEF increased by about 5% in the BMC group (from 53.8%±9.2% at baseline to 58.6%±9.9% at follow-up, P<.05), while LVEF decreased in the control group (from 58.2%±7.5% at baseline to 56.3%±3.5% at follow-up). In the study conducted by Suárez de Lezo et al, 4 the average increase in the ejection fraction exceeded 20% following intracoronary BMC treatment, the largest improvement reported to date (baseline: 37%±5%, followup: 58%±920%), while a significantly smaller increase (6%, P = .003) was observed in the control group (baseline: 39%±6%, follow-up: 45%±8%).…”
Section: Lvef Change Noted In Individual Studiesmentioning
confidence: 86%
“…Suárez de Lezo et al 4 defined LV dysfunction as angiographic ejection fraction <45%. In the studies by Ge et al 7 and Chen et al, 10 LV dysfunction was not defined.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
See 3 more Smart Citations